Pécs gazdasági helyzete a 19. század közepén - Kaposi, Zoltán (Közép-Európai Közlemények, 2017)
Pécs has been the largest city of the South-Transdanubian region for centuries. It had been a market town of the Church for a long time yet it was given the rank of royal free city in 1780. In the first part of the 19th century there was a quick economic development in the city. This resulted that Pécs became the most important trade centre of the South-Transdanubian region, its agglomeration was the second largest after Pest. The economy of the city stood on many pillars. Its 13000-acre frontier served the purpose of raising crops, keeping livestock and practicing forestry. Speciality of the city was the huge 1800-acre vineyard; due to this Pécs was one of the most important settlement nationally when it came to wine trading. Industrialisation was growing stronger in the 1830s. Beside the traditional handicraft and guilds more and more modern businesses were founded. Manufactories and plants were spreading and coal mining got under way. The first savings bank was founded in 1845. With its population of 15000 Pécs became the cultural centre of the region in the middle of the 19th century.